1988
DOI: 10.1515/corrrev.1988.8.1-2.35
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical characterization of some commercial inhibitor used for acid cleaning of steam generators

Abstract: The behaviour of four commercial inhibitors used for the pickling baths and acid cleaning of steam generators in thermal power stations has been investigated and their inhibitor effectiveness has been determined both with gravimetrical tests and with electrochemical measurements. The latter have shown that a complete surface impedance diagram on Argand's plane is very helpful in discriminating the behaviour of a given corrosion inhibitor, quantitatively as well as qualitatively.In addition, numerical elaborati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…1250. The code utilizes the galvanostatic mode and performs measurements at the free corrosion potential over the frequency interval [7,13] kHz with a fixed integration time corresponding to 2000 cycles.…”
Section: Capacitance Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1250. The code utilizes the galvanostatic mode and performs measurements at the free corrosion potential over the frequency interval [7,13] kHz with a fixed integration time corresponding to 2000 cycles.…”
Section: Capacitance Methodsmentioning
confidence: 99%
“…Usually the interval [7,13] kHz is examined when reference electrodes such as SCE and Ag-AgCl are used, because experience shows that the response of the electrochemical system is not distorted by the electrode dynamic. Wider interval amplitudes can be examined when metallic reference electrodes are used.…”
Section: Capacitance Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is necessary to underline that the last two remarks are not restricted to the case under discussion, but our experience has shown that they have a general validity both for pure compounds [29] and for commercial inhibitors [30]. Table 3, concerning the solution inhibited with 0.05 g l -I of inhibitor, compares the values of C obtained with the three methods.…”
Section: Iron In Inhibited Hcl Solutionsmentioning
confidence: 98%